Supporting the use of adjuvant radiotherapy in recurrent pleomorphic adenoma of the parotid. (1st October 2021) - Hintze, Justin M.; O'Duffy, Fergal; White-Gibson, Ailbhe; O'Neill, Paul; Kinsella, John; Timon, Conrad; Lennon, Paul
Abstract: Background: The use of adjuvant radiotherapy remains controversial in the treatment of recurrent pleomorphic adenomas. Aims/objectives: The aim of this study was to provide the highest level of evidence possible by performing a systematic review and meta-analysis of the literature. Material and methods: We searched the English-language literature between 1985 and 2019.Inclusion criteria included any study on the treatment and outcome of recurrent pleomorphic adenomas. Exclusion criteria included the use of radiotherapy for residual tumors, case reports, and pleomorphic adenomas not arising from the parotid. Results: A total of 522 abstracts were studied, data analyzed from 14 studies, on a total of 697 patients. When the data werepooled, the overall risk of further recurrence was 21%. In studies where surgery alone was undertaken this increased to 26% and decreased to 10% in those receiving adjuvant radiotherapy ( p = .000). There were 21 recurrences in 159 patients in the radiotherapy group, and 151 recurrences out of 538 patients in the surgery group ( p < .0001). Conclusions: These data support the use of radiotherapy to decrease the risk of re-recurrence in recurrent pleomorphic adenoma. Significance: This study is the highest level of evidence currently available in guiding management of recurrent pleomorphic adenoma.